Teacher Professional Competence: Comparative Analysis of Certified and Non-Certified Teachers (Case Study at SMPIT Al-Husna Kubang Jaya) - Milarahma Putri, Dea Wanda; Mila Alvionita; Harly, Muhammad Riadhi; Afriza (Global Action and Education for Society, 2025)
The purpose of this research is to determine how certified teachers and non-certified teachers differ in professional competence at SMPIT Al-Husna Kubang Jaya. A comparative research type is used in this study, and the data collection method is through questionnaires. In this study, five certified teachers and five uncertified teachers were taken as samples, with the population serving as a saturated sample. This study uses questionnaires to collect data. To identify differences between groups, the data analysis technique used a t-test for two samples with a significance level of 5%. The results of the data analysis using the t-test show that the professional competence variable has a significant value of 0.201 ≥ 0.05. Therefore, H0 is accepted and Ha is rejected, indicating that there is no difference between certified teachers and non-certified teachers. In the sample of 10, the t-table value is 3.169, so 0.201 ≤ 3.169 at a significance level of 0.005. This means that Ha is rejected and Ho is accepted, resulting in no significant difference in professional competence between certified and non-certified teachers at SMPIT Al-Husna Kubang Jaya. In other words, teachers who are not certified do not necessarily lack professional competence.